ANALYSIS OF THE APPLICABILITY OF THE ANIVI-STURTEVANT DYNAMIC CLASSIFIER IN THE PRODUCTION OF CRUSHED AGGREGATES - Vokurka, Michal; Zegzulka, Jiri; Hummel, Martin; Dobiáš, Jiří (Journal of Applied Engineering Science, 2025)
The presented paper analyses the applicability of the Anivi-Sturtevant dynamic classifier in production of crushed aggregate in a quarry. This dynamic air classifier allows separation of fine particles of smaller sizes than 0.063 mm from materials that have excessive amounts of these particles. This is executed in order to recover materials that would otherwise be deposited only as waste materials. The research included an experiment in a quarry following predefined methodology. By regular sampling of materials and their subsequent testing, the particle size distributions of grains were plotted, and also depending on the input moisture or due to the separation of fine particles. The operation of the classifier consumes electrical energy and from this point of view, it is necessary to monetize the output profitably. A modelling process has been implemented where the 0/4 mm fraction produced by Anivi is mixed into the commonly produced fraction 0/4 certified or into mixtures of 0/32 or 0/63.